Xyloglucan-Based Hybrid Nanocomposite with Potential for Biomedical Applications - Casagrande-Denardin, J (Elsevier B.V., 2021)
Natural polymer-based hybrid nanocomposites have been proposed as one of the most promising tools for biomedical applications, including disease treatment and diagnosis procedures. Xyloglucan nanocapsules can simultaneously load magnetic iron oxide nanoparticles and bioactive for a specific tissue, reducing the processes of degradation and metabolic inactivation of molecules with biological activity. In this work, magnetic nanocapsules of xyloglucan loaded with hydrophilic sulfated quercetin (MNXQ_SO3) were successfully synthesized by inverse miniemulsion process through interfacial polymerization. The polymeric shell formation of nanocapsules was evidenced by Fourier Transform Infrared spectroscopy and Transmission Electron Microscopy. The ferrofluid (Fe3O4@PAAS) incorporated into the xyloglucan nanocapsules was synthesized by hydrothermal method, using polyacrylic acid sodium salt as coating. Dynamic Light Scattering technique confirmed the nanomeric dimensions (202.3 nm) and the good colloidal stability (−40.2 mV) of MNXQ_SO3. The saturation magnetization analyses pointed out the superparamagnetic behavior of Fe3O4@PAAS (48 emu/g) and MNXQ_SO3 (4.2 emu/g). MNXQ_SO3 was able to modify the release profile of sulfated quercetin (67%) when compared to the free bioactive (100%), exhibiting a release profile compatible with the zero-order kinetic model. The results showed that the development of MNXQ_SO3 presents a new perspective for biomedical applications, including studies of targeted drug delivery. © 2020 Elsevier B.V.